Rethinking Grounds: Migration, Anthropocene and Covid-19 - Khalid, Sadaf; Ahmad, Farhan; Apakina , Liudmila Vyacheslavovna; Banu, Sameena (Journal of Education Culture and Society, 2024)
Thesis. The paper highlights Anthropocene challenges during Covid-19 and student’s struggle. The Anthropocene is debatable because to its emphasis on human primacy and humanism, as well as the ways in which it conceals problematic aspects of human diversity, such as gender and cultural disparities, and the close ties that exist between people, technology and other creatures along with its relationship with migrations. Concept. A rising number of individuals now depend on migration for their livelihoods on a global scale. However, the migration processes of industrialised and developing nations have significantly differed. In contrast to industrialised countries, where migration is more driven by pull reasons like wealth, safety, and freedom than by push causes like poverty, unemployment, regional inequities, family movement, marriage, and natural disasters, such as those in India. The greatest modern challenge is figuring out how to lessen the effects of the physical and biological changes brought about by human activity on a global scale in a new geological era known as the Anthropocene. Results and Conclusion. The paper confirms the significance of interactions between humans and the environment is underappreciated in the present definitions of globally linked systemic risk. This leads to a bias in favour of solutions that downplay the Anthropocene’s new realities. The present study confirms a comprehensive understanding of the dangers associated with the Anthropocene and migration, or hazards that arise from processes of human-driven migration, interact with the world’s social-ecological interconnection.